Mesh generation for confined fusion plasma simulation. (April 2016) - Zhang, Fan; Hager, Robert; Ku, Seung-Hoe; Chang, Choong-Seock; Jardin, Stephen; Ferraro, Nathaniel; Seol, E.; Yoon, Eisung; Shephard, Mark
Abstract XGC1 and M3D-C 1 are two fusion plasma simulation codes being developed at Princeton Plasma Physics Laboratory. XGC1 uses the particle-in-cell method to simulate gyrokinetic neoclassical physics and turbulence (Chang et al. Phys Plasmas 16(5):056108, 2009; Ku et al. Nucl Fusion 49:115021, 2009; Admas et al. J Phys 180(1):012036, 2009). M3D- C^1 C 1 solves the two-fluid resistive magnetohydrodynamic equations with the C^1 C 1 finite elements (Jardin J comput phys 200(1):133–152, 2004; Jardin et al. J comput Phys 226(2):2146–2174, 2007; Ferraro and Jardin J comput Phys 228(20):7742–7770, 2009; Jardin J comput Phys 231(3):832–838, 2012; Jardin et al. Comput Sci Discov 5(1):014002, 2012; Ferraro et al. Sci Discov Adv Comput, 2012; Ferraro et al. International sherwood fusion theory conference, 2014). This paper presents the software tools and libraries that were combined to form the geometry and automatic meshing procedures for these codes. Specific consideration has been given to satisfy the mesh configuration and element shape quality constraints of XGC1 and M3D- C^1 C 1 .